1997
DOI: 10.1128/iai.65.8.3218-3224.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in Helicobacter pylori-induced interleukin-8 production by a gastric cancer cell line, MKN45

Abstract: Accumulating evidence suggests an important role of interleukin-8 (IL-8) in Helicobacter pylori infectionassociated chronic atrophic gastritis and peptic ulcer. We observed in this study that a gastric cancer-derived cell line, MKN45, produced a massive amount of IL-8 upon coculture with live H. pylori but not with killed H. pylori, H. pylori culture supernatants, or live H. pylori separated by a permeable membrane, indicating that IL-8 production requires a direct contact between the cells and live bacteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(108 citation statements)
references
References 42 publications
7
99
1
1
Order By: Relevance
“…[58][59][60] Moreover, it has been shown that activation of both AP-1 and NF-ĸB is involved in the regulation of Il8 gene expression in MKN45 cells in response to H. pylori infection. 61 Additionally, overexpression of Pellino2 has been demonstrated to activate the ERK and JNK MAPK pathways, 44 and inhibition of Pellino2 expression attenuates TLR4-mediated activation of these kinases and the induction of proinflammatory cytokine genes. 62 As such, it is possible that Pellino2 regulates chemokine expression through pathways involving the MAPK axis of the TLR2-mediated response.…”
Section: Pellino1mentioning
confidence: 99%
“…[58][59][60] Moreover, it has been shown that activation of both AP-1 and NF-ĸB is involved in the regulation of Il8 gene expression in MKN45 cells in response to H. pylori infection. 61 Additionally, overexpression of Pellino2 has been demonstrated to activate the ERK and JNK MAPK pathways, 44 and inhibition of Pellino2 expression attenuates TLR4-mediated activation of these kinases and the induction of proinflammatory cytokine genes. 62 As such, it is possible that Pellino2 regulates chemokine expression through pathways involving the MAPK axis of the TLR2-mediated response.…”
Section: Pellino1mentioning
confidence: 99%
“…Both MAPK and NF-κB pathways culminate in the activation of several pro-inflammatory target genes, including the IL-8 gene (Aihara et al, 1997). Hence, we determined the potential of P12ΔhopQ to stimulate IL-8 secretion in AGS cells compared with P12 wild type and P12ΔcagPAI.…”
Section: The Hopq Defect Broadly Impairs Activation Of Cag-t4ss-depenmentioning
confidence: 99%
“…Also the T4SS itself induces host cell responses in gastric epithelial cells such as the activation of the transcription factor NF-κB (Glocker et al, 1998). Together with the transcription factor AP-1 (activator protein 1), NF-κB regulates the expression of interleukin 8 (IL-8) (Aihara et al, 1997;Sharma et al, 1998) and is involved in cellular apoptotic, proliferative and immune responses (Hoffmann and Baltimore, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which the CPI enhances IL-8 secretion is unknown, but attachment to the mucosa appears critical [39,40]. For example, when a membrane is placed between H. pylori and the target cells, the pro-inflammatory activity was [40]. Whether internalization is also critical has not been addressed [40,41].…”
Section: Caga Is a Marker For Enhanced Inflammationmentioning
confidence: 99%
“…For example, when a membrane is placed between H. pylori and the target cells, the pro-inflammatory activity was [40]. Whether internalization is also critical has not been addressed [40,41].…”
Section: Caga Is a Marker For Enhanced Inflammationmentioning
confidence: 99%